2016
DOI: 10.5152/iao.2016.1998
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Percutaneous Bone-Anchored Hearing Aid Abutment Systems: Comparative Clinical Study

Abstract: OBJECTIVE:To compare two different percutaneous bone-anchored hearing aid (BAHA) abutment systems regarding operation time, scar healing, quality of life, implant stability, audiologic results, and complications. MATERIALS and METHODS:The study involves a prospective multi-center clinical evaluation. Thirty-two consecutive patients who had undergone BAHA surgery from January 2011 to January 2013 in two tertiary centers were included in the study. The Glasgow Inventory Benefit Score was used to assess the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Full text review of these 290 articles was conducted, and a total of 52 articles were selected for inclusion (Fig. 1) (13–64). Critical appraisal of studies indicated an acceptably low risk of bias for the majority of included studies (Fig.…”
Section: Resultsmentioning
confidence: 99%